147k views
2 votes
What are the steps they're using to simplify this?

What are the steps they're using to simplify this?-example-1
User Brinda K
by
5.0k points

1 Answer

4 votes

Answer: Distribute, Combine like terms, factor, & simplify

Explanation:


.\quad ((x+h)^2+9(x+h)-(x^2+9x))/(h)\\\\=(x^2+2xh+h^2+9x+9h-x^2-9x)/(h)\quad \rightarrow\ \text{Distributed}\\\\=(2xh+h^2+9h)/(h)\quad \rightarrow\ \text{Combined like terms}\\\\=(h(2x+h+9))/(h)\quad \rightarrow\ \text{Factored}\\\\=2x+h+9\quad \rightarrow\ \text{Simplified}

User Mchouhan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.